A refined technique for extraction of extracellular matrices from bacterial biofilms and its applicability. Issue 3 (23rd August 2014) - Chiba, Akio; Sugimoto, Shinya; Sato, Fumiya; Hori, Seiji; Mizunoe, Yoshimitsu
Summary Biofilm‐forming bacteria embedded in polymeric extracellular matrices (ECMs) that consist of polysaccharides, proteins and/or extracellular DNAs (eDNAs) acquire high resistance to antimicrobial agents and host immune systems. To understand molecular mechanisms of biofilm formation and maintenance and to develop therapeutic countermeasures against chronic biofilm‐associated infections, reliable methods to isolate ECMs are inevitable. In this study, we refined the ECM extraction method recently reported and evaluated its applicability. Using three Staphylococcus aureus biofilms in which proteins, polysaccharides or eDNAs are major contributors to their integrity, ECMs were extracted using salts and detergents. We found that extraction with 1.5 M sodium chloride (NaCl) could be optimum for not only ECM proteins but also polysaccharides and eDNAs. In addition, long‐time incubation was not necessary for efficient ECM isolation. Lithium chloride (LiCl) was comparative to NaCl but is more expensive. In contrast to SDS, NaCl hardly caused leakage of intracellular proteins and did not affect viability of bacterial cells within biofilms. Furthermore, this method is applicable to other bacteria such as Gram‐positive Staphylococcus epidermidis and Gram‐negative Escherichia coli and Pseudomonas aeruginosa. Thus, this refined method is very simple, rapid, low cost and non‐invasive and could be used for a broad range of applications.